Source analyses of axial and vestibular evoked potentials associated with brainstem-spinal reflexes show cerebellar and cortical contributions. (13th July 2021) - Todd, Neil P.M.; Govender, Sendhil; Lemieux, Louis; Colebatch, James G.
Highlights: Short latency potentials were evoked over the posterior fossa with vestibular and axial stimuli. Source analysis showed potentials arose predominantly from within the cerebellum and medial forebrain. Cerebellar excitability changes preceded soleus EMG by approximately 45 ms. Medial forebrain activations may facilitate subsequent voluntary responses. Abstract: In this work we examine the possible neural basis for two brainstem-spinal reflexes using source analyses of brain activity recorded over the cortex and posterior fossa. In a sample of 5 healthy adult subjects, using axial and vestibular stimulation by means of applied impulsive forces, evoked potentials were recorded with 63 channels using a 10 % cerebellar extension montage. In parallel, EMG was recorded from soleus and tibialis anterior muscles and accelerometry from the lower leg. Recordings over the cerebellum (ECeG) confirmed the presence of short latency (SL) potentials and these were associated with changes in high-frequency power. The SL responses to the two stimulus modalities differed in that the axial stimulation produced an initial pause and then a burst in the high-frequency ECeG, followed by excitation/inhibition in soleus while vestibular stimulation produced an initial burst then a pause, followed by inhibition/excitation in soleus. These short latency responses were followed by longer latency N1/P2/N2 responses in the averaged EEG, which were maximal at FCz. Brain Electrical Source Analysis (BESA) demonstrated both cerebellar and cerebral cortical contributions to the short-latency responses and primarily frontal cortex contributions to the long-latency EPs. The latency and polarity of the SL EPs, in conjunction with changes in high-frequency spontaneous activity, are consistent with cerebellar involvement in the control of brainstem-spinal reflexes. The early involvement of frontal cortex and subsequent later activity may be an indicator of the activation of the cortical motor-related system for rapid responses which may follow the reflexive components. These findings provide evidence of the feasibility of non-invasive electrophysiology of the human cerebellum and have demonstrated cerebellar and frontal activations associated with postural-related stimuli.